Dilema Umat Islam Dalam Keterkaitan Memilih Pemimpin Di Indonesia Pasca Reformasi “ Tinjauan Dari Surat (An-Nisâ’/4:59)” Dan Hadis Nabi (Shahih Al-Bukhari,: 1765) - Mahmuda muda (Politik Islam, 2024)
Indonesia is one of the countries in the world that is unique, including being the largest Muslim country in the world, and being a country with a plurality of other religions apart from Islam. Talking about Indonesiacannot be separated from talking about Muslims, an inseparable part before independence until independence from colonial invaders. The influence of Islamic teachings in Indonesia is reflected in the many freedom fighters who fought against colonialism so that they could unite the jihad spirit of the people of the entire archipelago in defending independence.The problem that arises in this reform era is the dilemma of Muslims in determining whose attitude isgood in leading .. This is a big dilemma as Muslims in determining who is a worthy candidate for leadership to be elected. Therefore, the author assumes that this issue is considered very urgent to be discussed, because the issue of leadership is also a very sensitive religious issue if examined closely.